2006
DOI: 10.1037/0735-7044.120.1.72
|View full text |Cite
|
Sign up to set email alerts
|

The effects of orbital frontal cortex damage on the modulation of defensive responses by rats in playful and nonplayful social contexts.

Abstract: In a series of 3 experiments on rats, 2 hypotheses were tested: (a) that damage to the orbital frontal cortex (OFC) would alter the socially relevant context for executing defensive responses but not their performance and (b) that damage done to the OFC in early infancy would produce more deficits in social behavior than similar damage occurring in adulthood. Bilateral or unilateral OFC damage in adult males did not impair their ability to defend themselves during play fighting and when protecting their food b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
103
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 68 publications
4
103
1
Order By: Relevance
“…In keeping with these findings, the structure of social play and its sensitivity to social cues was found to be altered after neonatal lesions of the PFC or OFC (Bell et al, 2009;Panksepp et al, 1994;Pellis et al, 2006;Schneider and Koch, 2005).…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…In keeping with these findings, the structure of social play and its sensitivity to social cues was found to be altered after neonatal lesions of the PFC or OFC (Bell et al, 2009;Panksepp et al, 1994;Pellis et al, 2006;Schneider and Koch, 2005).…”
Section: Introductionsupporting
confidence: 56%
“…Although the neural substrates of social play behavior are incompletely understood (Siviy and Panksepp, 2011;Trezza et al, 2010;Vanderschuren et al, 1997), there is evidence to support a role for the prefrontal cortex (PFC) and striatum in the regulation of social play behavior (Bell et al, 2009;Panksepp et al, 1994;Pellis et al, 1993Pellis et al, , 2006Schneider and Koch, 2005;Trezza et al, 2011Trezza et al, , 2012. As it is in these regions that profound neural changes occur during the juvenile and adolescent period (Casey and Jones, 2010;Crone and Dahl, 2012;Spear, 2000), the abundance of social play behavior suggests that play is related to the maturation of the PFC and striatum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early research on RTP was done on nonhuman animals. The RTP of rats, hamsters, monkeys, and chimpanzees is fairly well-described [Chalmers, 1983;Paquette, 1994;Pellis, 1987, 1988] and studies have clearly established links between RTP and frontal-lobe functioning [Burgdorf et al, 2006;Panksepp et al, 2003;Pellis et al, 2005Pellis et al, , 2006 and socialization, particularly in primates [Hughes, 1991;Millar, 1968]. Although adults often confuse RTP with genuine aggression [Scott and Panksepp, 2003], research has clearly distinguished these two types of behaviors [Jones, 1972] and demonstrated that they arise from two distinct motivational systems, one associated with affiliation and the other with competition [Panksepp, 1998a;Paquette, 1994;Pellis et al, 2005].…”
Section: Play and Socializationmentioning
confidence: 99%
“…The parietal cortex has been shown to activate in self-interested economic decision making, especially expected utility calculations (14)(15)(16). Neural networks involved in social rewards also have been heavily researched (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Of particular interest to us is the orbitofrontal cortex (OFC), which is known to be reliably involved in social reward evaluation and decision making processes (15,17,19,(28)(29)(30)(31).…”
mentioning
confidence: 99%